Political economy of the 2014 farm bill - Orden, David; Zulauf, Carl (Wiley, 2015)
This article assesses the political economy of the 2014 U.S. farm bill, with a focus on the farm support safety net. The farm bill secured substantial bipartisan majorities in a politically contentious Congress. Planned outlays are predominately for nutrition assistance programs directed toward a traditional nonfarm constituency in the farm bill coalition, while annual fixed direct payments to farmers are eliminated but replaced with enhanced downside risk protection against low prices or revenue. The new support programs may prove more or less costly than the foregone fixed payments, with farmers offered a choice between a price countercyclical program with increased reference prices and a revised moving‐average revenue guarantee program. The role of insurance is enhanced, notably by replacing past support programs with a new upland cotton revenue insurance program and dairy milk‐to‐feed margin protection program. Open policy issues that are highlighted include the costs and distortionary effects of moving‐average revenue benchmarks versus fixed reference prices, the overall level of insurance premium subsidies, the potential for overlap between commodity and insurance programs, and lastly, food, environmental, and biofuels concerns that reflect the diverse portfolio of products demanded from agriculture. In an international context, we conclude that the 2014 farm safety net likely would not have been enacted had multilateral agreement been reached on the 2008 Doha Round World Trade Organization negotiating documents. Conversely, the 2014 farm bill makes achieving those limits more difficult. Research is discussed that can elucidate the ongoing political economy of U.S. farm policy and help shape future program design.